2019
DOI: 10.1103/physrevd.100.044061
|View full text |Cite
|
Sign up to set email alerts
|

Parametrized black hole quasinormal ringdown. II. Coupled equations and quadratic corrections for nonrotating black holes

Abstract: Linear perturbations of spherically symmetric spacetimes in general relativity are described by radial wave equations, with potentials that depend on the spin of the perturbing field. In previous work [1] we studied the quasinormal mode spectrum of spacetimes for which the radial potentials are slightly modified from their general relativistic form, writing generic small modifications as a power-series expansion in the radial coordinate. We assumed that the perturbations in the quasinormal frequencies are line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 96 publications
(153 reference statements)
4
87
0
Order By: Relevance
“…In a similar way, we also showed that δV can be rewritten in terms of (r H /r) j with only low j using the ambiguity of the effective potential. It is also interesting to extend the present discussion to the coupled cases and the higher order cases [6], but we leave them for future work.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…In a similar way, we also showed that δV can be rewritten in terms of (r H /r) j with only low j using the ambiguity of the effective potential. It is also interesting to extend the present discussion to the coupled cases and the higher order cases [6], but we leave them for future work.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Finally, let us point that such disformal transformation of the Schwarzschild stealth solution provides a straightforward way to build minimal hairy deformation of vacuum GR solution which are exact solution of a DHOST theory. Up to now, such minimal deformation of the vacuum solutions of GR have been introduced for phenomenological investigation and remain ad hoc [70]. Using the new exact solution (4.35), and performing a linear expansion in term of the parameters A • and B • , our solution generating method allows instead to endow these phenomenologically interesting geometries within the effective approach of DHOST theories.…”
Section: Starting From a Stealth Solutionmentioning
confidence: 99%
“…Going beyond these consistency tests requires modeling the BH ringdown beyond GR, for instance to perform a Bayesian model selection between GR and any proposed extension of the theory. This is a challenging task and, despite recent progress [37][38][39][40][41][42][43][44], all current attempts have significant limitations: they are based on particular classes of theories, they use geometric-optics approximations for the QNMs, or they neglect the spin of the remnant.…”
Section: Introductionmentioning
confidence: 99%
“…The above discussion suggests that a case-by-case analysis is impractical, and that parametrizing directly the observables (i.e., frequencies and damping times) is the most efficient way to perform ringdown tests (see e.g. [22,27,42,43] for work in this direction). Similar observable-based approaches have been very successful to model weak-field effects [73] and the inspiral [74,75].…”
Section: Introductionmentioning
confidence: 99%